Semarak Keluarga UMP celebrates festive merdeka - Mohd. Mukhris, Awang (2022)
PAYA BESAR, 30 August 2022 – More than 600 students from Universiti Malaysia Pahang (UMP) were excited to celebrate the 65th National Day of Malaysia after two years of no celebrations held following the Movement Control Order (MCO).